2004
DOI: 10.1111/j.1399-3046.2004.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel immunosuppressants

Abstract: Advances in maintenance immunosuppression over the past decade has resulted in dramatic improvements in short- and long-term outcomes in organ transplantation as well as a decreased incidence of acute rejection. However, immunosuppressive drugs need to be given long term, lack specificity, and are accompanied by adverse metabolic derangements, toxicities, the risk of infection and cancer, and a myriad of other side effects. Further, they fail to prevent and control chronic rejection. This review will outline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Of the other agents currently under investigation, there are only preliminary data on everolimus and the paediatric age group [63,64]. Tolerance strategies or strategies to minimise immunosuppression may provide some protection against both immune injury and CNI toxicity.…”
Section: New Therapiesmentioning
confidence: 96%
“…Of the other agents currently under investigation, there are only preliminary data on everolimus and the paediatric age group [63,64]. Tolerance strategies or strategies to minimise immunosuppression may provide some protection against both immune injury and CNI toxicity.…”
Section: New Therapiesmentioning
confidence: 96%
“…Therapeutic interventions to such diseases are often designed to reduce the threshold of T cell activation [16]. Therefore, immnosuppressive drugs, like cyclosporine A (CsA) and dexamethasone (Dex), are often used in these immune overwhelming diseases [20,21] In the present study, we found that icaritin at a quite low concentration could act as an immunosuppressant to reduce T cell proliferation, IL-2/CD25 expression, and Th1 cytokines production in vitro. To confirm the immune suppressive effect of icaritin in vivo, mouse skin transplantation, the standard model to assay host T cell responses to MHCdisparate donor antigens [22], was selected.…”
Section: Introductionmentioning
confidence: 93%
“…Immunosuppression can be accomplished by depleting cells, inducing tolerance, preventing the production of proinflammatory mediators, or blocking cell surface receptors (1,2). The predominant immunosuppressive drugs presently in clinical use consist of glucocorticoids and calcineurin inhibitors.…”
mentioning
confidence: 99%